Kadar Serat, Sifat Organoleptik dan Daya Terima Permen Jelly Kulit Buah Naga Merah (Hylocereus Costaricencis) - Dwi Node Julianti; Teguh Supriyono; Mars Khendra Kusfriyadi; Agnescia Clarissa Sera (Jurnal Forum Kesehatan, 2018)
Due to its anthocyanin and betacyanin content, dragon fruit skin can be used as a natural dye in food. Dragon fruit skin which has been regarded as waste is also high in fiber. Both potential functions can be applied into jelly candy product. This experimental study with Completely Randomized Design (CRD) was specifically intended to determine the effect of 6 formulations of dragon fruit skin concentrations (10%, 20%, 30%, 40%, 50% and 60%) on their fiber contents, organoleptic properties and consumer acceptability of dragon fruit skin jelly candy. Kruskal-Walls Test (α = 0.05) was used to test the data. If there is a difference, data was proceeded by using the Mann-Whitney Test (α = 0.05). There was a significant difference between the concentration of dragon fruit peel extract and fiber content (p = 0.00). The highest fiber content was found in jelly candies with a concentration of 60% dragon fruit skin. There was no significant effect between the concentration of dragon fruit peel extract on aroma (p = 0.25) and taste (p = 0.08) jelly candy. There is a significant difference between the concentration of dragon fruit peel extract on texture (p = 0.00) and colour (p = 0.00) jelly candy. In terms of aroma, taste, texture and colour, most of panellist preferred jelly candy with dragon fruit skin concentration of 40%. The higher the concentration of dragon fruit peel extract, the higher the level of jelly candy fiber. The concentration of dragon fruit skin extract affects the texture and colour attributes of jelly candy